Relationship between the systemic immune-inflammatory index and overactive bladder risk: A cross-sectional assessment involving United States Adults - Peng Zheng; Xiaoqian Wang; Junjie Ni (PLoS ONE, 2025)
Aims This study aimed to evaluate the association between the systemic immune-inflammatory index (SII) and the risk of overactive bladder (OAB) in the adult United States population. Methods Data from the National Health and Nutrition Examination Survey (NHANES) 2005–2010 were analyzed. A non-pregnant cohort aged ≥20 years with available SII and OAB data was included. Weighted univariate and multivariate logistic regression analyses were performed to assess the association between SII and OAB risk. Additionally, subgroup, interaction, and restricted cubic spline analyses were conducted. Results A total of 4,545 participants were included, of whom 16.13% had OAB, with a mean SII of 5.75 ± 0.07. OAB risk increased with higher SII tertiles. In the fully adjusted model (Model 2), individuals in the highest SII tertile exhibited a 41% higher risk of OAB compared to those in the lowest tertile (OR: 1.41, 95% CI: 1.13–1.76, P = 0.004). Two-piece-wise regression analysis identified an SII breakpoint at 3.40, where a significant positive association was found for SII ≥ 3.40 (OR = 1.06, P < 0.0001), whereas no significant association was detected for SII < 3.40 (P = 0.06). Subgroup and interaction analyses revealed a consistent relationship between SII and OAB across different population strata, except for diabetes mellitus. Conclusion SII, an easily accessible biomarker, was independently associated with an increased risk of OAB, highlighting its potential utility in diagnostic prediction.